2016
DOI: 10.1017/s1431927616011697
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Containing Restorations Create Amorphous Biogenic Apatite at the Carious Dentin Interface: A X-Ray Diffraction (XRD) Crystal Lattice Analysis

Abstract: The aim of this research was to assess the ability of amalgam restorations to induce amorphous mineral precipitation at the caries-affected-dentin substrate. Sound and cariesaffected dentin surfaces were subjected to both Zn-free and Zn-containing dental amalgam restorations. Specimens were submitted to thermocycling (100,000cy/5 ºC-55 ºC, 3 months).Dentin surfaces were studied by atomic force microscopy (AFM/nano-roughness), X-ray diffraction (XRD 2 ), field emission electron microscopy (FESEM) and energy-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Our proteomics results also revealed that SRPs might play more important roles than LRPs for NRB in H. brasiliensis [ 8 ]. Laticifer cells were considered to originate from a series of cells united by dissolution of intervening walls [ 35 ]. It was reported that in TKS seedlings, as early as 10 days after germination, small rubber particles start to form in the laticifer cells, and these rubber particles have similar morphological patterns to those in other rubber-producing plants, such as H. brasiliensis and Parthenium argentatum [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our proteomics results also revealed that SRPs might play more important roles than LRPs for NRB in H. brasiliensis [ 8 ]. Laticifer cells were considered to originate from a series of cells united by dissolution of intervening walls [ 35 ]. It was reported that in TKS seedlings, as early as 10 days after germination, small rubber particles start to form in the laticifer cells, and these rubber particles have similar morphological patterns to those in other rubber-producing plants, such as H. brasiliensis and Parthenium argentatum [ 35 ].…”
Section: Discussionmentioning
confidence: 99%